The importance of European collaborations to support Open Science and digital library development - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
This paper looks at the distinguished career of Pat Manson and identifies key themes in her work on digital libraries. It then takes those themes, as Pat prepares for well-deserved retirement, and sketches out the challenges which face libraries and European organisations in 2016. The themes chosen are: Open Science, Copyright reform and Open Access to Publications. The paper concludes that while libraries now have a voice at European top tables, the challenge is to fine tune that voice in order to create and deliver infrastructure, policies and services which support Open Science in the twenty-first century.